Suicide attempt in the adolescence: un approach from primary health care - Ana Milena Perez Arteaga; Mercedes Carballea Barrera; Luis Alejandro Valdés López; Irismenia Valdés Cruz (Centro para el Desarrollo de las Ciencias Sociales y Humanísticas en Salud, 2020)
Introduction: Suicide attempt is an extrem demonstration of violence, for being against himself, in the world and Cuba are in expansion. Objective: characterize suicide attempt in adolescence, socio-demography aspect, risk factors associated to attempt, personals and familys antecedent of precedent suicide attempt. Methods: It was descriptive and cross sectional study, the target group was comprissed for 81 adolescents, the sample was not probabilist and consisted of 46 adolescents. The tests used were inquiry for the control and type of the suicide behavior, individual interview and family interview. Apply empiric and statistic method and data was process with Word XP, table and graph make with Excel XP. Results: among the main results were that the most frequents age was 15 to 19 years, school level high school, marital status single and they weren't working. Alcoholism and imitation were the community risk factors and as individual risk factors couple breaking, depression and self-characteristic. Discussion: we arrived to the following conclusions that the persons who planned the suicide attempt and used a hard method had die intention. There is a relationship between the use of hard method and die intention, between the use of soft method and the intention to call the attention.